Rail passengers' preferences for onboard Wi-Fi internet access - O'MAHONY, MARGARET MARY (My University, 2009)
This paper presents the results of a survey which was conducted on an Irish Rail service to ascertain how the value of travel time may change if individuals could partake in another activity while travelling. The survey included a stated preference section which uses a multinomial logit (MNL) model to estimate the benefits individuals would derive from having access to the internet while they travel on public transport. In the survey, respondents were asked would they rather have wi-fi internet access throughout the train or in segregated wi-fi carriage. The results from this study show that multi-tasking while travelling by rail is extremely common, with the majority of respondents participating in two or more activities. The most frequent form of multi-tasking was the use of a mobile phone. This study examined the potential for wi-fi internet access while travelling by public transport. The results found that approximately two thirds of respondents said if wi-fi internet access was available they would use it once or more every week.
88th Annual Meeting of the Transportation Research Board
PUBLISHED
Washington D.C.
Keywords: Civil, Structural & Environmental Engineering